Pengembangan E-LKPD Matematika Berbasis HOTS pada Materi Bangun Ruang Prisma dan Limas SMP Kelas VIII - Khotimah, Khusnul; Istinganah, Siti; Umardiyah, Fitri; Nasrulloh, M Farid (JoEMS (Journal of Education and Management Studies), 2022)
This research is a development research or R&D (Research and Development) which aims to produce and describe HOTS-based mathematics E-LKPD learning media. This research uses the ADDIE type of development model. Based on the results of the data analysis, the validity of the material experts obtained an average score of 3.43 with valid criteria, and media experts obtained an average score of 3.48 with valid criteria. The results of the students' responses to the HOTS-based mathematics E-LKPD obtained a percentage of 85,69% with the good criteria. The learning outcomes in the Pre-test knowledge obtained an average value of 36.75, which means that overall students scored below the KKM, namely 70. While the learning outcomes in the Post-test knowledge assessment obtained an average value of 80.62, which means Overall, students scored above the KKM, namely 70. Based on these data, it can be concluded that the HOTS-based mathematics E-LKPD on prism and pyramid building materials is declared valid, practical, and effective so that it is suitable for use in learning.